Finger doses due to 68Ga-labelled pharmaceuticals in PET departments—results of a multi-centre pilot study. (1st March 2023) - McCann, Ann; Cherbuin, Nicolas; Covens, Peter; Dabin, Jérémie; Haruz-Waschitz, Sigalit; Gallo, Lara; Datz, Hanan; Wierts, Roel; Wrzesien, Malgorzata; Zorz, Alessandra; Cooke, Jennie; Dowling, Anita; et al.
Abstract: Introduction: Although the use of 68 Ga has increased substantially in nuclear medicine over the last decade, there is limited information available on occupational exposure due to 68 Ga. The purpose of this study is to determine the occupational extremity exposure during the preparation, dispensing and administration of 68 Ga-labelled radiopharmaceuticals. Method: Workers in eight centres wore a ring dosimeter for all tasks involving 68 Ga-labelled radiopharmaceuticals for a minimum of one month. Additionally, the fingertip dose was monitored in two centres and the hand with the highest ring dose during 68 Ga procedures was also identified in one centre. Results: The median normalised ring dose for 68 Ga procedures was found to be 0.25 mSv GBq −1 (range 0.01–3.34). The normalised 68 Ga ring doses recorded in this study are similar to that found in the literature for 18 F. This study is consistent with previous findings that the highest extremity dose is found on the non-dominant hand. A limited sub study in two of the centres showed a median fingertip to base of the finger dose ratio of 4.3. Based on this median ratio, the extrapolated annual 68 Ga fingertip dose for 94% of the workers monitored in this study would be below Category B dose limit (150 mSv) and no worker would exceed Category A dose limit (500 mSv). Conclusion: When appropriate shielding and radiation protection practices are employed, the extremity dose due to 68 Ga is comparable to that of 18 F and is expected to be well below the regulatory limits for the majority of workers.